IMPLEMENTASI KARTU JAWA TENGAH SEJAHTERA (KJTS) DI KECAMATAN BOJA KABUPATEN KENDAL TAHUN 2020-2022 - Ramadhani, Dito Arya; Manar, Dzunuwanus Ghulam; -, Yuwanto - (Journal of Politic and Government Studies, 2024)
The number of poor people in Kendal Regency exceeded 8 thousand people, indicating the magnitude of the poverty problem in the area. Central Java Governor Regulation Number 40 of 2017 showed seriousness in overcoming poverty and helping those who were unproductive through the implementation of the Central Java Prosperous Card (KJTS). This research was conducted to understand the implementation of the KJTS policy in Kendal Regency, using George Edward III's theory which included aspects of communication, resources, disposition, and bureaucratic structure. Data was collected through interviews, and qualitative data analysis was carried out by data triangulation. The subjects in this research were the Boja District Government, Kendal Regency Social Service employees and Central Java Province Social Service employees. The research results showed that the implementation of KJTS in Kendal Regency could be used as a model of accuracy and effectiveness in the distribution of social assistance. This program placed emphasis on comprehensive verification and validation procedures, as well as utilized data analysis through the Integrated Social Welfare Data system. This ensured a targeted approach in beneficiary selection. By responding to the needs of individuals with special conditions and encouraging inclusivity through proposals from underserved villages, KJTS showed a commitment to reaching those who truly needed help